Discriminating Rankings of Research in Business - Sönke Albers (ZBW - Leibniz-Informationszentrum Wirtschaft, 2009)
The attempts by Schulze, Warning, and Wiermann (2008) and Ritzberger (2008) to develop a joint ranking list of journals for economics and business research are critically evaluated. Their lists suggest that the quality of top business journals is substantially lower than that of many economics journals. If, however, the authors of these lists do not want to claim a general superiority of one discipline (economics) over another one (business), they should give a clear indication that these lists are only applicable for economists. This warning appears necessary because Fabel, Hein, and Hofmeister (2008) derive a ranking of universities and departments with respect to research productivity in business from the business research discriminating list RbR_IMP by Schulze et al. While Diamantopoulos and Wagner (2008) already show a lack of face-validity of these results, this article explains that the reason for this lies not only in the degrading and also biased weighting of the business journals across subfields, but even more importantly, in a remarkable incompleteness of the data base.
Keywords: A12; I23; M00; 650; Journal ranking; University ranking